HOW HAS THE UNEMPLOYMENT BENEFITS SHAPED THE EUROPEAN LABOUR MARKET? : The implications of unemployment benefits generosity on unemployment longevity - Ngiendo, Charles (My University, 2022)
Unemployment and the unemployment rates are strongly associated with labour market participation. The principal aim of the study was to investigate the relationship between unemployment benefits generosity and the labour market outcome in terms of prolonged unemployment in the European context. The aim was also to provide information that will lay the groundwork for investigating the efficacy of unemployment benefits on the labour market outcome in terms of unemployment longevity for causal inference and social policy evaluation. This study seeks to answer the question: does generous unemployment compensations increase the job search duration? The research methods involved the use of analytical techniques for the quantitative determination of influence of unemployment compensation on unemployment spell. The data was obtained from 25 European countries, with the unemployment duration (from 1 to 12 months) for a period of fifteen years (from 2004 to 2019) and a total of 425,656 observations. Multilevel regression (mixed effects with restricted maximum likelihood, REML) was used. Results showed that more generous unemployment compensations have a positive relationship with unemployment duration thus generous unemployment benefits increase the unemployment durations. The country-level replacement rates are positively correlated with unemployment spells.
Keywords: compensation, EU, labour market, social policy, unemployment benefits, unemployment longevity